THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE EMPLOYEES OF THE WATER RESOURCES AND PUBLIC WORKS AGENCY MULYOREJO WORK UNIT SURABAYA CITY - Sutikno Sutikno; Anang Kistyanto; Dewi Tri Wijayati Wardoyo (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The aim of this research is to examine and analyze the effect of compensation on motivation, the effect of motivation on performance, the effect of motivation and work environment on performance through performance satisfaction as an intervening variable for employees of the Water Resources and Highways Service in the Mulyorejo Rayon Work Unit. This research uses a type of causal research with a quantitative approach. The research location is at the Water Resources and Highways Service Office, Tandes Rayon Work Unit, Jl. Kalidami IX, Mojo Village, Gubeng District, Surabaya, East Java. The population in this study were non-ASN/task force employees of the Water Resources and Highways Service of the Mulyorejo Rayon Work Unit, totaling 112 task forces. The sampling technique used Slovin's opinion, so the number of samples taken was 82 non-ASN/task force employees. Information is collected by submitting a questionnaire. The data analysis method used is SEM (Structural Equation Model) based on Partial Least Square (PLS) with software Smart-PLS 3. The results of the study indicate that work motivation does not affect employee performance. Meanwhile, the work environment has a positive effect on employee performance. Furthermore, work motivation has a positive effect on job satisfaction, while the work environment does not affect job satisfaction. Furthermore, job satisfaction has a positive effect on employee performance. In an indirect relationship, job satisfaction acts as a mediator in the relationship between motivation and employee performance, but does not act as a mediator in the relationship between the work environment and employee performance.